Four Eyes: Two Views on Social Media for Science Communication (2018)
A conversation between Jorge Bonilla and Javier Cruz where the new narratives are discussed on social networks, there are scenarios of journalism and scientific communication on social networks, they talk about the abundance of information and the difficulty of finding truthfulness because the main information actors are anonymous people or without any training in journalistic strictness